Review of small cell carcinoma of the kidney with focus on clinical and pathobiological aspects - Kuroda, Naoto; Imamura, Yoshiaki; Hamashima, Takeru; Ohe, Chisato; Mikami, Shuji; Nagashima, Yoji; Inoue, Keiji; Perez-Montiel, Delia; Petersson, Fredrik; Michal, Michal; Hes, Ondrej (Polish Journal of Pathology, 2014)
Small cell carcinoma (SmCC) of the kidney is extremely rare. In this article, we present a review of SmCC of the kidney with the focus on clinical and pathobiological aspects. Macroscopically, this tumor often shows a bulky mass extensively replacing the renal parenchyma with vascular invasion and metastasis to lymph nodes. Histologically, the tumor is composed of small cells with scant cytoplasm, round to oval nuclei, finely granular chromatin and inconspicuous nucleoli. Rosette or tubular formation may be present. Immunohistochemically, neoplastic cells show variable positivity for neuron-specific enolase, chromogranin A, synaptophysin, CD57 (Leu7) and CD56. A dot-like staining pattern for cytokeratin may also be observed. An electron microscopic examination may identify electron-dense neurosecretory granules in the cytoplasm. As a therapeutic option, nephrectomy and systemic chemotherapy should be considered. However, despite multimodal therapy, most patients have a dismal outcome and die of widely metastatic disease within one to two years. As there are limited genetic data on SmCC of the kidney, a large series studying this will be needed in the future.